PERCEPTION PAYSANNE SUR LA FRAGMENTATION FORESTIÈRE ET SES CONSÉQUENCES SUR LA BIODIVERSITÉ DANS LA RÉGION DE BENGAMISA, EN TERRITOIRE DE BANALIA, (RD. CONGO). - Elysée, KASONGO WALO; Marc, BOKETSHU ILONGA; BESINGELA BOLOMBI Esaïe; Léon, IYONGO WAYA MONGO (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2021)
This present study designed on the forest fragmentation and its different consequence on biodiversity in the Bengamisa sector is on analysis of the population of this environnemnt on the appreciation of the quality of the inhabitants and orientation of developpment properties it’s about avaluating the level of the deterioration of the forest landscape in this envuronment as well as the resulting consequences.